2021
DOI: 10.1016/j.heliyon.2021.e06757
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of copper slag for beneficiation of iron and copper

Abstract: Before disposal of any metallurgical waste to the environment, it is the responsibility of mining institutes to adhere to the permissible metal content limits. Base metals, especially iron and copper, have adverse effects of reducing the soil pH and excessive concentrations of these in the disposed waste may result in soil pollution and toxicity, with adverse effects on plant growth and animal health. Copper slag is a metallurgical waste that is disposed by way of stockpiling at designated dump sites within a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 19 publications
(33 reference statements)
0
16
0
Order By: Relevance
“…Four series of grinding tests were conducted using a laboratory batch scale ball mill (Version, Sepor, Los Angeles, CA, USA) that operated at 66 rpm (1.1 Hz) corresponding to 70% of its critical speed, under dry conditions, as seen in Table 2. The grinding media consisted of balls with various sizes and density 7.85 g/cm 3 , corresponding to ball filling volume J = 20%, while the material filling volume f c was 4%. Consequently, the interstitial void space of the balls U that is filled with slag was kept constant at 50%, as shown in Equation (7).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Four series of grinding tests were conducted using a laboratory batch scale ball mill (Version, Sepor, Los Angeles, CA, USA) that operated at 66 rpm (1.1 Hz) corresponding to 70% of its critical speed, under dry conditions, as seen in Table 2. The grinding media consisted of balls with various sizes and density 7.85 g/cm 3 , corresponding to ball filling volume J = 20%, while the material filling volume f c was 4%. Consequently, the interstitial void space of the balls U that is filled with slag was kept constant at 50%, as shown in Equation (7).…”
Section: Methodsmentioning
confidence: 99%
“…where S w is the specific surface area, ρ p is the particle density, D [3,2] is the mean surface area (Sauter mean diameter), and f, k are the surface and volume coefficients (for spheres f /k = 6).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As During high-temperature process, the oxide components of the slag form low melting phases as a result of chemical reactions, e.g., fayalite Fe 2 [SiO 4 ] (T M = 1205 • C) [8,9], cuprite Cu 2 O (T M = 1215 • C) [10], magnetite Fe 3 O 4 (T M = 1539 • C) [11], and lead silicate Pb 2 SiO 4 (T M = 747 • C) [7]. Therefore, since the 1950s, the most suitable refractories for Cu production have been magnesia-chromite refractories produced from chromite ore and sintered or fused magnesia.…”
Section: Oxidementioning
confidence: 99%
“…In previous studies, the initial characterization of smelter slag was followed by the proposal of a process route to utilize the slag. The slag can be characterized using Xray diffraction (XRD), Fourier-transform infrared spectroscopy (FTIR), scanning electron microscopy with energy-dispersive spectrometry (SEM-EDS), and light optical microscopy (LOM) in transmitted and reflected light [45][46][47]. Previous studies have indicated that copper slag behaves differently when subjected to different temperatures, thus exhibiting different properties [42,48].…”
Section: Uses Of Metallurgical Slagmentioning
confidence: 99%